Content analysis of advergames in food and beverage brand websites aimed at children: immersive marketing practices in scoring systems of advergames - Kim, Sookyong (Kansas State University, 2010)
Since 2000s, advergames, a particular form of branded entertainment that features advertising messages, logos, and trade characters in a game format, have become popular. The impact of advergmaes on childhood obesity, however, has been concerned among consumer groups and parents. Advertisers may use advergame scoring systems to encourage children to consume junk foods, to persuade them to revisit the Websites to help them to become addicted to the games, to reinforce children’s bad eating habits in advergames with voices or rewards, and to attract children with animated spokes characters and avatars. The purpose of this study is to examine in-depth components of scoring systems of advergames, providing policy makers and researchers with insights about advergames. Brand integration in scoring systems of advergames appeared on food companies’ websites was explored with the descriptive characteristics of the roles of brands, such as gaming tools or equipment or main objects or in the backgrounds of games. A content analysis of 67 food companies’ websites aiming to children will be done to critically evaluate the practice of online food marketing and advergames targeting children. Results of this study indicates that the prevalence of junk food (e.g., snack foods, sweets, convenience entrees and meals and soft drinks, and artificially flavored beverages), different types of brand integration (e.g., secondary objects or primary objects) in advergames scoring systems, virtual food consumption and food brand exposures to children in advergames, and the behavior of animated characters used in scoring systems in advergames. Understanding the immersive marketing of scoring systems in food advergames can provide valuable insights into how to establish appropriate regulations for online food marketing to children.
Keywords: children; Journalism (0391)